Algas epífitas indicadoras de calidad del agua en arroyos vinculados a la Laguna de los Padres - Esquiús, K. S. (2008)
Diatoms constitute a useful tool to evaluate the trophic status of aquatic systems, as they answer quickly to environmental changes. They have been used in water quality researches since the beginning of the 20th century, but only few reports are available from Argentina. In the present paper, several biological descriptors have been employed to evaluate the water quality of the influent and effluent streams from Los Padres Lagoon (Los Padres and La Tapera creeks, respectively), including Descy Index (DI) and Pampean Diatoms Index (PDI). In each creek, ten stems of the «giant bulrush» (Schoenoplectus californicus) were randomly collected and the main physical and chemical parameters were recorded in situ. In the laboratory, periphyton was removed and algae taxa were identified and counted. A total of 107 periphytic taxa were identified (83 at the inflow and 101 at the outflow). Diatoms constituted the richest and the most abundant group in both creeks. DI and PDI indices showed a higher eutrophic level in the influent, possibly due to the input of an important quantity of agricultural polluents of the surrounding lands and to the strong impact of birds. Species composition, diversity and equitability were the only biological descriptors suitable to assess the water quality in the present study.